2022
DOI: 10.1002/cbic.202200409
|View full text |Cite
|
Sign up to set email alerts
|

Proline C−H Bonds as Loci for Proline Assembly via C−H/O Interactions

Abstract: Proline residues within proteins lack a traditional hydrogen bond donor. However, the hydrogens of the proline ring are all sterically accessible, with polarized CÀ H bonds at Hα and Hδ that exhibit greater partial positive character and can be utilized as alternative sites for molecular recognition. CÀ H/O interactions, between proline CÀ H bonds and oxygen lone pairs, have been previously identified as modes of recognition within protein structures and for higher-order assembly of protein structures. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…Interestingly, the difluoroproline carbonyl exhibited a close C–H/O interaction , with chloroform (H···O distance 2.25 Å) (Figure b), as well as a C–H/O interaction (2.60 Å) between one ProHβ and the carbamate carbonyl (Figure d). These observations are consistent with our recent report that C–H/O interactions are a general mode for structure stabilization and molecular assembly at proline residues …”
Section: Resultssupporting
confidence: 94%
“…Interestingly, the difluoroproline carbonyl exhibited a close C–H/O interaction , with chloroform (H···O distance 2.25 Å) (Figure b), as well as a C–H/O interaction (2.60 Å) between one ProHβ and the carbamate carbonyl (Figure d). These observations are consistent with our recent report that C–H/O interactions are a general mode for structure stabilization and molecular assembly at proline residues …”
Section: Resultssupporting
confidence: 94%
“…C-H/O interactions are inherently favorable at the polarized C-H bonds of proline. 17 We observed that C-H/O interactions can stabilize all type VI β-turn subtypes.…”
Section: The Cis-proline Conformation Is Stabilized By C-h/o Interact...mentioning
confidence: 70%
“…In order to examine Ser– Pro structures via small-molecule X-ray crystallography, we synthesized dipeptides with the unnatural proline derivative (2 S ,4 S )-(4-iodophenyl)hydroxyproline [hyp(4-I-Ph)] (Scheme 1). 17,29,30 This amino acid promotes crystallization via the aryl iodide. The aryl iodide has also been employed for further amino acid modification via Suzuki or Sonogashira cross-coupling reactions, which can be conducted on peptides in water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthrochelin A 6 is a growth-promoting metallophore of the human pathogen Luteibacter anthropi. 5 The biosynthetic pathway to anthrochelin A 6 had been studied using genome analyses and stable isotope labelling. Anthrochelin A 6 contains the unusual C-terminal homocysteine but there is no module for the incorporation of this amino acid.…”
mentioning
confidence: 99%